GAMBARAN PENGGALIAN DAN PEMBERIAN INFORMASI OBAT ATTAPULGITE DI APOTEK KECAMATAN BANJARMASIN TIMUR - Ratih Pratiwi Sari; Erna Prihandiwati (Jurnal Insan Farmasi Indonesia, 2019)
The practice of self-medication in cases of diarrhoea is important to do, including extracting and providing correct drug information. The purpose of this study was to determine the description of extracting and providing information by pharmacists on patients who bought attapulgite drugs at the pharmacy in the East Banjarmasin area. This study is a non-experimental study conducted in March until July 2018, with samples used by all pharmacy staff working in pharmacies in the East Banjarmasin area. The results of this study indicate that the profile of attapulgite drug extraction information includes the identity of the patient (25%), frequency of bowel movements (16.66%), other symptoms (0%), what drugs have been used to treat diarrhea (0 %), other drugs being used (4.16%), patient history (0%), allergy history of patients (0%), non-pharmacological actions to treat diarrhea (0%), history of diarrhea (0%) and other questions (8.33%). The results of the profile research giving information show that the method of using the drug (25%), drug interactions (0%), side effects (0%), and frequency of use (8.33%).